Politeness in Europe - Hickey, Leo; Stewart, Miranda, 1954- (Multilingual Matters S., V.127., 2005)
Politeness as practised across 22 European societies, firmly set within critical debates developed since the 1980s, is here presented in ways related to concrete situations in which language-users interact with one another to achieve their goals.